Perinatal determinants of patent foramen ovale and neurological implications: towards biomarker-guided precision medicine - Bosco, Alice; Dessì, Angelica; Giorri, Sara (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2025)
The growing expansion of modern high-throughput technologies has paved the way for precision medicine, which aims to stratify patients, personalize therapeutic indications, and potentially prevent long-term consequences. In this context, the presence of the patent foramen ovale (PFO) is reinterpreted, shifting from a benign anatomical variant to a possible indicator of cardiovascular and neurological vulnerability. The concept of perinatal programming offers an interpretative model for understanding how early environmental and biological conditions can modulate cardiovascular adaptation and predisposition to neurological disorders, such as migraine with aura (MWA). Numerous studies have shown a higher prevalence of PFO in patients with MWA, although only some patients benefit from percutaneous closure. This led to the creation of the MANET project (NRRP-MAD-2022-12376277), a pioneering model of precision medicine, in which the analysis of the metabolic profile of patients with MWA undergoing percutaneous PFO closure and the subsequent integration of platelet and endothelial data will be aimed at constructing a combined model of biomarkers capable of guiding the selection of patients with MWA who are potential beneficiaries of PFO closure, optimizing the therapeutic approach. These multidisciplinary and multicenter research projects represent an ideal lab for facilitating the transition from a vision focused exclusively on the morphology of atrial septal defects to a broader perspective that links developmental biology to neurological manifestations in adults.